Optimalisasi Fungsi Masjid Sebagai Pusat Pendidikan Dan Pemberdayaan Masyarakat (Studi Kasus KKN Rekognisi Di Kemuning, Palembang) - Isabella, Vitria; Rindang; Eva Andini; Rhessya Putri Wulandari Tri Maris (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to describe the optimization of the function of the mosque as a center of education and community empowerment through a participatory approach in the KKN Rekognisi activity by UIN Raden Fatah Palembang students at the Nurul Khoirot Mosque. The method used is descriptive qualitative with a case study approach. Data were obtained through activity reports, field documentation, and reflections of KKN participants, then analyzed thematically. The results of the study indicate that mosques can function optimally in non-formal education through the TPA program to strengthen the ability to read the Qur'an and Islamic values, tutoring as academic support for elementary school children, and creative writing classes to foster literacy and expression skills. In addition, social activities such as tadarus, yasinan, morning exercise, and breaking the fast together make the mosque a space for social interaction that strengthens relationships between residents and students. This program has a positive impact on increasing children's participation in learning activities, forming learning habits outside of school, and growing public awareness of the strategic role of mosques. This model can be replicated in various regions.